Comprehensive evaluation of thermal, structural, magnetic, and radiation shielding properties of CuAlNi and CuAlNi-X (X = Co, CoFe, CoFeMn, CoFeMnCr) high-temperature shape memory alloys - Ozkul, Iskender; Karaduman, Oktay; Simsek, Telem; Simsek, Tuncay; Canbay, Canan Aksu; Guler, Omer; Tekin, H. O. (Springer Heidelberg, 2025)
This study investigates the thermal, structural, magnetic, and radiation shielding properties of CuAlNi-based high-temperature shape memory alloys (HTSMAs) enhanced through sequential alloying with Co, Fe, Mn, and Cr. Five different variants were produced, designated as CRef (reference CuAlNi alloy), CCo (CuAlNiCo), CFe (CuAlNiCoFe), CMn (CuAlNiCoFeMn), and CCr (CuAlNiCoFeMnCr). Differential scanning calorimetry (DSC) confirmed the presence of reversible martensitic transformations in all alloys, with Co and Mn additions significantly enhancing thermal stability. Structural analyses using X-ray diffraction (XRD) and microscopy showed significant grain refinement and phase transitions, while magnetic measurements highlighted the strong ferromagnetic response of CCo (CuAlNiCo) and the increased coercivity of CMn (CuAlNiCoFeMn) due to domain-pinning effects. Moreover, radiation shielding analyses demonstrated the critical influence of density and elemental composition, with CRef exhibiting superior linear attenuation coefficients (LAC), effective atomic number (Zeff), and energy absorption buildup factor (EBF) performance, attributed to its optimized Cu fraction and high density (7.1296 g/cm3). In contrast, CMn (CuAlNiCoFeMn) showed the weakest shielding properties due to reduced density and Mn content. Among the samples, CRef emerged as the superior alloy, demonstrating exceptional multifunctionality across all evaluated parameters, while CCr (CuAlNiCoFeMnCr) displayed synergistic properties, combining shape memory behavior with competitive shielding efficiency. It can be concluded that CuAlNi-based HTSMAs hold significant potential as multifunctional materials, particularly for nuclear safety and aerospace engineering applications, where adaptive functionality and radiation protection are critical.
Keywords: Sequential alloying; CuAlNi alloy; DSC; Radiation shielding; Magnetic properties; Shape memory alloy